Caring for adult patients who die in the emergency department: Reflections of emergency room nurses - Hogan, Kerry-Anne (University of Ottawa (Canada), 2009)
Background. Emergency room nurses work in an area in which the workload is unpredictable and chaotic. Treatment measures are usually aggressive and the goal of care in the emergency department is to restore physiological stability in a sick or injured person. As treatment measures usually occur quickly and nurses care for many patients throughout their shifts, there is often a lack of time to establish relationships with patients and/or family members. In a situation when treatment is needed immediately, there may not be enough time to discuss advanced directives with patients and/or family members. Although most patients are seen, treated and sent home or are admitted and recover, more than 7000 lives end in Canadian emergency departments each year (CIHI, 2006). Death in an emergency department is almost always considered a tragic event, regardless of whether the event was unexpected or expected. This view contrasts with the idealistic view of death occurring in a hospice or at home, free of pain and suffering and surrounded by loved ones. In an emergency department, treatment of critical illnesses and/or injuries begins immediately, leaving nurses or other members of the team little time to discuss advance directives or establish rapport with patients and/or family members. Purpose. The purpose of this research study was to improve our understanding of the experience of emergency room nurses when caring for an adult who dies in the emergency department.
Keywords: Health Sciences, Nursing.